Brotes de rabia humana transmitida por vampiros en los municipios de Bajo y Alto Baudó, departamento del Chocó, Colombia 2004-2005 (2022)
eng: The human rabies outbreak in Bajo Baudó has been the largest reported in Colombia. It was caused by vampire bats, showing that these animals are a threat for human health. The implementation of control strategies for this kind of epizootic outbreaks is needed in South America. It remains unknown whether there is a link between this outbreak and one reported 6 months later in the neighboring municipality of Alto Baudó.